(3JGQjN GdCTQGa GdPjf edch GdMQejf GdTQjajfs - (3YHO Gddg Hf eMeO YHO GdTchQs ((3GdGSJGfI s)
(3ChdgG (B:s
(3deG QCjJ GMhGd GdReGf cd Mjf JJZjQ hGdOgQ CHh GdZjQ , hgh YHQI def GYJHQ s
(3BNQgG (B:s
(3hGWdb QbGH GdfGS ef GdCSQ , hedcJ GdWQbGJ hJQc GdMUQ , aJhGLOJ GdCbhGJ ef cd GdLgGJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3eJaQbGJs